2021
DOI: 10.1158/0008-5472.can-20-1441
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Antitumor Immunity via Endocrine Therapy Prevents Mammary Tumor Relapse and Increases Immune Checkpoint Blockade Sensitivity

Abstract: The role of active antitumor immunity in hormone receptor–positive (HR+) breast cancer has been historically underlooked. The aim of this study was to determine the contribution of the immune system to antiprogestin-induced tumor growth inhibition using a hormone-dependent breast cancer model. BALB/c-GFP+ bone marrow (BM) cells were transplanted into immunodeficient NSG mice to generate an immunocompetent NSG/BM-GFP+ (NSG-R) mouse model. Treatment with the antiprogestin mifepristone (MFP) inhibited growth of 5… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 47 publications
1
15
0
Order By: Relevance
“…Thus, adding anti-PD-1 or anti-PD-L1 antibodies on the top of auranofin/cisplatin combination therapy seems a rational combinational therapeutic approach. This idea is further supported by recent literature showing that breast cancer tissues were sensitive to mifepristone-an antiprogestin and antiglucocorticoid agent [140], which was able to induce ICD and thus synergize with PD-L1 blockade [141]. We previously reported that the anti-cancer effects of mifepristone [142,143] were associated with the induction of proteotoxic ER stress [144], a pathway needed to be active for ICD to succeed.…”
Section: New Viewpoint Of Research With Auranofin Against Cancer: the Link With Platinum-based Chemotherapy Immunogenic Cell Death And Immentioning
confidence: 61%
“…Thus, adding anti-PD-1 or anti-PD-L1 antibodies on the top of auranofin/cisplatin combination therapy seems a rational combinational therapeutic approach. This idea is further supported by recent literature showing that breast cancer tissues were sensitive to mifepristone-an antiprogestin and antiglucocorticoid agent [140], which was able to induce ICD and thus synergize with PD-L1 blockade [141]. We previously reported that the anti-cancer effects of mifepristone [142,143] were associated with the induction of proteotoxic ER stress [144], a pathway needed to be active for ICD to succeed.…”
Section: New Viewpoint Of Research With Auranofin Against Cancer: the Link With Platinum-based Chemotherapy Immunogenic Cell Death And Immentioning
confidence: 61%
“…Indeed, not all cell-death inducers can elicit the intracellular stress pathways that operate upstream of DAMP release in dying cancer cells (see below). Clinically actionable ICD inducers include specific conventional chemotherapeutics (for example, cyclophosphamide, anthracyclines, oxaliplatin and other platinum derivatives, but not cisplatin) 10,[36][37][38][39][40] , RT 41 and select targeted anticancer agents (for example, bortezomib, crizotinib) [42][43][44][45][46][47][48] , as well as some variants of endocrine therapy 49 , extracorporeal photochemotherapy 50 , photodynamic therapy (PDT) [51][52][53][54] and oncolytic virotherapy 55,56 . As a general principle, the release of DAMPs by malignant cells succumbing to these agents involves either alterations of the cell surface (for example, owing to the translocation of intracellular proteins to the external leaflet of the plasma membrane) or changes of the…”
Section: Immunogenic Cell Stress and Deathmentioning
confidence: 99%
“…On the other hand, progestagens reconfigure the breast cancer microenvironment, inducing the preferential expansion of myeloid-derived suppressor cells in the spleen and bone marrow of tumor-bearing mice [ 355 ]. Furthermore, anti-progesterone treatments enhance the anti-tumor immune response and increase sensitivity to the PD-L1 blockade in breast cancers [ 356 ]. It is worth noting that progesterone regulates galectin-1 expression in some experimental settings [ 357 , 358 ].…”
Section: Discussionmentioning
confidence: 99%